THE RELATIONSHIP BETWEEN POTENTIAL OF VACCINE AND IMMUNIZATION SERVICES WITH QUALITY OF MEASLES VACCINE IN KONAWE KEPULAUAN DISTRICT: Measles vaccine - Afiat Afiat; Timbul Supodo; Sunarsih Sunarsih (STIKes Mandala Waluya Kendari, 2021)
Background:Based on a report from the Directorate General of Disease Prevention and Control (P2P) of the Ministry of Health, the development of measles cases in Indonesia in 2016 was 7,204 cases. In 2017 there were 11,389 cases, where this year there were many measles outbreaks. In 2018 there were 3,995 cases, the actual number of cases was still higher but many were not reported. In 2019 there were 6,419 reported cases. Methods: This type of research is an observational analytic study with a cross sectional study design. The population was the measles vaccine which was found in 8 health centers withThe sample size was 82 Vaccine for Measles. Result: Statistical test using kai squared analysis at ? = 5% and df = 1, obtained the value of X2 count> X2 table 32,210> 3,841 and ? = 5% and df = 1, obtained the value of X2 count <X2 table 1.247 <3,841 potential relationships and immunization services for the quality of measles vaccine in Konawe Islands District. Conclusion: There is a strong relationship between vaccine potential and the quality of the measles vaccine and there is no relationship between immunization services and the quality of the measles vaccine in Konawe Islands District.